Daily doses of COVID-19 vaccine administered in the world (Revista de Investigaciones Universidad del Quindío, 2023)
Introduction: The COVID-19 pandemic, produced by SARS-CoV-2, continues to be a global public health crisis. COVID-19 messenger RNA (mRNA) vaccines, including mRNA-1273 (Moderna) and BNT162b2 (Pfizer-BioNTech), are highly effective in preventing SARS-CoV-2 infections and COVID-19 hospitalizations. Objective: to show the countries with the highest daily doses per 100 inhabitants in percentage and the absolute change in daily doses for COVID-19, between December 1, 2021, and January 7, 2022. Methodology: this research was carried out under a cross-sectional study; the information was obtained from the website of the information collected by Our World in Data COVID-19. Results: It was determined that the countries with the highest absolute changes in applied dose for COVID-19 in percentage were Gibraltar (321.02), Cuba (253.08), Chile (23.66), United Arab Emirates (219.9), Brunei (87.27), Singapore (216.94). Conclusion: Beyond access to vaccines, countries should not minimize the need for resources at the local level to carry out national vaccination plans against COVID-19. In this sense, to administer the vaccines it is necessary to have installed capacity, especially at the first level of care, and availability of supplies.
Keywords: COVID-19; SARS-CoV-2; pandemic; vaccines